An insight into microelectronics industry wastewater treatment, current challenges, and future perspectives: a critical review - Efaq Ali Noman, Efaq Ali Noman; Adel Ali Al‑Gheethi, Adel Ali Al‑Gheethi; Mohammed Al‑Sahari, Mohammed Al‑Sahari; G. Yashni, G. Yashni; Radin Mohamed, Radin Maya Saphira; Chin Fhong Soon, Chin Fhong Soon; Hong‑Ha T. Nguyen, Hong‑Ha T. Nguyen; Dai‑Viet N. Vo, Dai‑Viet N. Vo (2024)
The microelectronics industry wastewater is attracting the scientifc community and industry attention due to the high amount of organic and inorganic pollutants produced. Pollutants in microelectronic wastewater are considered qualitative contaminants, found in low concentrations but present with high risks to the environment and public health. The current paper highlights the most common pollutants in microelectronics wastewater and discusses the recent treatment technologies used to remove these contaminates. The review process was conducted based on the identifcation and screening of microelectronic wastewater and the principle of contaminant detection reported in previous research literature. It appears that tetramethylammonium hydroxide and ammonium are the major organic compounds in microelectronic wastewater, while heavy metals are among the inorganic pollutants with high environmental toxicity. The membrane fltration is the most efcient method for removing the pollutants (more than 90%) and producing ultrapure water. However, wastewater should be subjected to primary treatment using chemical and biological methods before undergoing the ultrafltration process. The zero-discharge concept is more applicable in the microelectronics industries due to the stringent regulations associated with these industries. Microelectronic sludge represents the main challenge in wastewater recycling, while advanced treatment methods have been suggested for sludge treatment. More efort is required to recycle microelectronics owing to the high prices related to the disposal of these solids’ wastes.